Intimate ethnography: What's it good for? - Waterston, Alisse (American anthropologist, 2025)
Anthropologist Barbara Rylko‐Bauer and I coined the term “intimate ethnography” in 2006 to capture the research and writing approach in our respective life‐history projects, she with her mother and I with my father. Since that time, the genre has seen growing recognition in anthropology. Intimate ethnography centers on an intimate other—family members or someone known to the ethnographer prior to the research—as the subject of an ethnographic project that is also a study of historical conditions and circumstances. Critical to intimate ethnography is attention to crafting accessible, evocative, and scholarly informed works that engage public conversation on serious sociocultural issues and political‐economic conditions, past and present. In this article, I define and describe intimate ethnography in relation to the original vision Rylko‐Bauer and I imagined for it. In doing so, I situate the genre in a series of intellectual concerns and conversations, sociocultural formations, and political circumstances and events from the writing culture debates to the politics of representation and discussions on ways to decolonize anthropology. In considering the value of intimate ethnography, I will assess its potential contributions and limitations in a time when the need to rethink and recount lives lived and experienced is increasingly urgent. RESUMEN La antropóloga Barbara Rylko‐Bauer y yo acuñamos el término “etnografía íntima” en 2006 para capturar la aproximación a la investigación y la escritura en nuestros respectivos proyectos de historias de vida, ella con su madre y yo con mi padre. Desde ese tiempo, el género ha visto un reconocimiento creciente en la antropología. La etnografía íntima se centra en un otro íntimo –miembros de la familia o alguien conocido por el etnógrafo con anterioridad a la investigación– como el sujeto de un proyecto etnográfico que es también un estudio de las condiciones y circunstancias históricas. Crucial a la etnografía íntima es la atención a una escritura accesible, evocativa y trabajos informados académicamente que estimulan la conversación pública sobre cuestiones socioculturales serias y condiciones político‐económicas, pasadas y presentes. En este artículo, defino y describo la etnografía íntima en relación con la visión original que Rylko‐Bauer y yo imaginamos para esta. Al hacerlo, sitúo el género en una serie de preocupaciones y conversaciones intelectuales, formaciones socioculturales y circunstancias y eventos políticos desde los debates de la cultura de escribir a la política de representación y discusiones sobre las formas de descolonizar la antropología. Al considerar el valor de la etnografía íntima, evaluaré sus contribuciones y limitaciones potenciales en un tiempo cuando la necesidad de repensar y recontar vidas vividas y experimentadas es crecientemente urgente. [Etnografía íntima, economía política, escribir antropología, métodos, historias]